Idiopathic retroperitoneal fibrosis: an unusual cause of low back pain - Nemec, Petr; Rybnickova, Sylva; Fabian, Pavel; Fojtik, Zdenek; Soucek, Miroslav (Clinical rheumatology, 2008)
Retroperitoneal fibrosis (RPF) is a rare inflammatory disease which is characterized by the development of a fibrous process that surrounds the major vessels and organs located within the retroperitoneum. About two thirds of all cases of RPF are idiopathic and are thought to be immunological in origin. Diagnosis of RPF should be considered in patients with unexplained abdominal and low back pain and retroperitoneal lesions. We present a case report of a 59-year-old white male with idiopathic RPF with history of low back pain and weight loss as only symptoms and treated by tamoxifen, corticosteroids, and insertion of JJ endoureteric catheters due to the obstruction of the upper urinary tract.
Keywords: Low Back Pain; Magnetic Resonance Imaging; lidé; tamoxifen; Retroperitoneal Fibrosis; lumbalgie; Estrogen Antagonists; Tamoxifen; magnetická rezonanční tomografie; Male; Humans; Middle Aged; retroperitoneální fibróza; antagonisté estrogenu; lidé středního věku; mužské pohlaví